ESG and Corporate Performance: A Review - Zhan Shuyuan (SHS Web of Conferences, 2023)
ESG is becoming increasingly important topic in corporate finance literature. In addition to developed countries, emerging market economies have also increased their attention on ESG in recent years. The number of papers on ESG published by finance and accounting journals skyrocketed. The effect of ESG on corporate performance is uncertain. This paper provides implications for investors, ESG can build up reputation, transmit positive signals, and investors react positively to socially responsible firms, increasing corporate performance. On the other hand, according to the agency theory, more ESG involvements may reflect managerial opportunism, which negatively affects corporate innovation. This paper aims to provide a synthetic and evaluation monograph of literature that examines the relationship between ESG and corporate performance.